A Review of Infrared Thermography for Condition-Based Monitoring in Electrical Energy: Applications and Recommendations - Balakrishnan G.K.; Yaw C.T.; Koh S.P.; Abedin T.; Raj A.A.; Tiong S.K.; Chen C.P. (MDPI, 2023)
Condition based maintenance; Condition monitoring; Deep learning; Fault detection; Infrared devices; Temperature indicating cameras; Condition-based monitoring; Electrical energy; Energy applications; Faults detection; High resolution infrared; Infra-red cameras; Infrared cameras; Non destructive; Non-contact; Thermal; Thermography (imaging)